Glucocorticoid-induced tumour necrosis factor receptor family related protein (GITR) mediates inflammatory activation of macrophages that can destabilize atherosclerotic plaques - Kim, Won-Jung (Blackwell Science Inc, 2006)
Glucocorticoid-induced tumour necrosis factor receptor family related protein (GITR) is the 18th member of the tumour necrosis factor receptor superfamily (TNFRSF18) and is known to interact with its cognate ligand GITRL (TNFSF18). We investigated the potential role of GITR in the pro-inflammatory activation of macrophages. Immunohistochemistry and in situ hybridization analyses of human atherosclerotic plaques demonstrated that GITR and its ligand are expressed mainly in lipid-rich macrophages. We then investigated the role of GITR in human and mouse monocyte/macrophage functions. Stimulation of GITR caused nuclear factor (NF)-κB-dependent activation of matrix metalloproteinase-9 (MMP-9) and pro-inflammatory cytokine expression in both the human and mouse monocytic/macrophage cell lines, THP-1 and RAW264.7, respectively. These cellular responses were also observed when the THP-1 cells were treated with phorbol-12 myristate-13 acetate (PMA), which is known to induce macrophage differentiation. To demonstrate that these responses are not restricted to cultured cell lines, we tested primary macrophages. Both peritoneal and bone marrow-derived macrophages responded to GITR stimulation with induction of MMP-9 and tumour necrosis factor-α (TNF-α). Furthermore, the GITR staining pattern overlapped with those of MMP-9 and TNF-α in atherosclerotic plaques. These data indicate that GITR-mediated macrophage activation may promote atherogenesis via the induction of pro-atherogenic cytokines/chemokines, and destabilize the atherosclerotic plaques via the induction of the matrix-degrading enzyme, MMP-9.